Enhanced greenhouse film with morphologically driven enhancement and differential scattering

The existing film materials are solved in terms of mechanical strength, optical properties and cost by using a combination of multimodal linear low-density polyethylene (LLDPE) and low-density polyethylene (LDPE) of at least 70% w/w in agricultural films. The shortcomings of the industry have achieved high-performance and low-cost agricultural membranes.

CN119403866APending Publication Date: 2025-02-07ABU DHABI POLYMERS CO LTD BOROUGE +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380047538.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-22
Filing Date
2023-06-20
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

Existing agricultural film materials have shortcomings in mechanical strength, ultraviolet degradation, insecticide resistance, light transmittance and thermal stability, especially low scattering effects and high cost EVA materials limit their application.

Method used

Using a film of multimodal linear low-density polyethylene (LLDPE) and low-density polyethylene (LDPE) of at least 70% w/w, the mechanical and optical properties of the film are improved by optimizing density, melt flow rate and layered structure. and economical.

Benefits of technology

The film is achieved with high intensity, good resistance to UV, moderately high light transmittance, low infrared transmittance and uniform mechanical properties, reducing costs while maintaining high haze and total transmittance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005190524220000101
    Figure BDA0005190524220000101
  • Figure BDA0005190524220000122
    Figure BDA0005190524220000122
  • Figure BDA0005190524220000151
    Figure BDA0005190524220000151
Patent Text Reader

Abstract

The invention relates to a film suitable for greenhouses. The films comprise at least 70% w / w of specific multimodal linear low density polyethylene (LLDPE) and low density polyethylene (LDPE), with desirable properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a film suitable for a greenhouse. Background Art

[0002] Plastic films are used in agriculture in order to increase plant yields. Usually, for this purpose, in particular for greenhouses, tunnels and ground coverings, vinyl polymer films are used. Typical examples of known vinyl polymer films used in such applications are LDPE (low density polyethylene) films and EVA (ethylene vinyl acetate) films. These materials are usually used in the form of monolayer films of varying thicknesses (usually between 50 and 250 μm). The requirements for such films are varied, and not all types of films can meet the needs with respect to all required properties. Typical requirements for agricultural films are as follows:

[0003] a) The membranes should have high strength and toughness so that they can be kept in place without risk of breakage while also being usable in adverse weather conditions such as strong winds, heavy rains, etc. In particular, the membranes should provide long-term durability through improved mechanical properties.

[0004] b) The film should provide good resistance to UV degradation and pesticides.

[0005] c) The film should provide high transmittance to direct light (sunny day) as well as diffuse light (cloudy day) so that the light transmittance required for plant growth in sunlight can be achieved on both sunny and cloudy days.

[0006] d) The film should provide a relatively low infrared transmittance in order to achieve thermal stability inside a greenhouse, for example to balance the extreme temperatures between hot days and cold nights.

[0007] e) The film should provide a reasonably high scattering of light transmission, i.e. the film should provide a considerable diffusing effect in order to reduce the impact of direct light on the seedlings while avoiding stark shadows that would block out certain areas under the film.

[0008] f) The film should provide protection against harmful UV radiation, ie the film should absorb at least a portion of the natural UV radiation.

[0009] Greenhouse films in particular require a balance of optical and mechanical properties.

[0010] As mentioned above, direct sunlight (i.e., non-scattered light) through greenhouse coverings can be harmful to seedlings. At the same time, direct sunlight also creates sharp shadows, preventing light from reaching all parts of crops grown in the greenhouse. Therefore, films that show higher haze are generally advantageous because such films diffuse incident light, but at the same time, in order to improve the growth rate of crops in the greenhouse, it is of course also important to ensure light transmittance. Therefore, haze should not impair the overall transmittance of sunlight through the film.

[0011] Prior art film materials have inter alia the following disadvantages: the film material shows a low degree of scattering, i.e. the film material has a low or no diffusion effect. Furthermore, EVA is a relatively expensive material, which limits its use in agricultural films. In order to improve the scattering effect of agricultural films, mineral fillers and coatings of the films with paints are widely used. However, this disadvantageously reduces the light transmittance, such as the light transmittance in PAR, while also reducing the mechanical strength of the film.

[0012] Thus, optimal films for agricultural use should provide the best balance of the advantageous properties indicated above, and such films should preferably combine at least high transmittance for direct and diffuse light in the photoactive range (PAR), while also providing sufficient mechanical strength. Summary of the invention

[0013] The present invention provides a single-layer or multi-layer film, the film comprising:

[0014] At least 70% w / w of a multimodal linear low density polyethylene (LLDPE) having a molecular weight of 910 to 940 kg / m 3 a density of 0.1 g / 10 min (measured according to ISO 1183-1 - method A) and an MFR5 of 0.40 to 0.85 g / 10 min (measured according to ISO 1133-1; 190° C., 5 kg load), and

[0015] Low-density polyethylene (LDPE),

[0016] The film has a dart impact (DDI; measured according to ISO 7765-1) of at least 800 g; a tear strength MD of at least 12 N (measured according to ISO 6383-2); and a ratio of tear strength (TD) / tear strength (MD) (both measured according to ISO 6383-2) of less than 2.5.

[0017] Surprisingly it has been found that films comprising at least 70% w / w of a specific multimodal linear low density polyethylene (LLDPE) and a low density polyethylene (LDPE) can achieve the desired property profile for agricultural films. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 The force and pull-off speed (ductility) curves are depicted for the core layer composition in Ref.1 (LLDPE (FB2230), 85% + 15% LDPE (FB3003)); the core layer composition in IE1 (LLDPE (LLDPE-A), 85% + 15% LDPE (FB3003)); and the core layer composition in IE2: (LLDPE (LLDPE-A), 85% + 15% LDPE (FB3003)).

[0019] FIG2 depicts the scattered intensity as a function of the azimuthal angle (chi), showing the orientation of the (110) and (200) reflections in the sample. Chi = 0 and 180° represent the machine direction MD, while chi = 90 and 270° represent the transverse direction TD (see Figure 2a ). Figure 2b The curve depicted in corresponds to the (110) reflection, while Figure 2c The curves depicted in correspond to the (200) reflection. Among these curves, the higher intensity curve (black square) corresponds to Ref.4, while the lower intensity curve (grey circle) corresponds to IE3. Specifically, Figure 2a Depicted are 2D WAXS patterns obtained on films with Debye ring assignment. The machine direction is north-south, while the transverse direction is east-west. Figure 2b The scattered intensity is plotted as a function of the azimuthal angle (Chi), showing the preferred orientation of the (110) plane in the film, where Chi = 0° and 180° represent the machine direction MD, and Chi = 90° and 270° represent the transverse direction TD. Figure 2c The scattered intensity as a function of the azimuthal angle (chi) is plotted, showing the preferred orientation of the (110) and (200) reflections in the sample, where Chi = 0° and 180° represent the machine direction MD, and Chi = 90° and 270° represent the transverse direction TD. Note: The scattered intensity as a function of the azimuthal angle in Ref. 4 is offset along the y-axis for easier visualization.

[0020] Figure 3a Depicted is a comparison of the skin layer morphology of (left) reference film Ref. 1 and (right) inventive film (IE1) for samples with 15% LDPE in the core layer.

[0021] Figure 3b Depicted is a comparison of the core layer morphology of (left) reference film Ref. 1 and (right) inventive film (IE1) for samples with 15% LDPE in the core layer.

[0022] Figure 4 Depicted are three-dimensional surface topography images of the reference film Ref. 1 with 15% LDPE in the core layer (top) and the inventive film IE1 with 15% LDPE in the core layer (bottom). DETAILED DESCRIPTION

[0023] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those of ordinary skill in the art to which the invention belongs. Although any methods and materials similar or equivalent to those described herein can be used in practice to test the present invention, preferred materials and methods are described herein. In describing and claiming the present invention, the following terms will be used according to the definitions set forth below.

[0024] Unless expressly indicated otherwise, the terms "a", "an", etc. refer to one or more.

[0025] If not indicated otherwise, "%" means percent by weight.

[0026] When referring to the weight percentages of the compositions and the ingredients contained therein, it is to be understood that the total amount of the ingredients does not exceed 100% (±1% due to rounding) according to the present invention.

[0027] The monolayer or multilayer film according to the present invention comprises:

[0028] At least 70% w / w of a multimodal linear low density polyethylene (LLDPE) having a molecular weight of 910 to 940 kg / m 3 a density of 0.1 g / 10 min (measured according to ISO 1183-1 - method A) and an MFR5 of 0.40 to 0.85 g / 10 min (measured according to ISO 1133-1; 190° C., 5 kg load), and

[0029] Low-density polyethylene (LDPE),

[0030] The film has a dart impact (DDI; measured according to ISO 7765-1) of at least 800 g; a tear strength MD of at least 12 N (measured according to ISO 6383-2); and a ratio of tear strength (TD) / tear strength (MD) (both measured according to ISO 6383-2) of less than 2.5.

[0031] Preferably, the film is an agricultural film, more preferably a greenhouse film.

[0032] Preferably, the multimodal linear low density polyethylene (LLDPE) has a 3 , more preferably 918 to 928 kg / m 3 and especially 920 to 926 kg / m 3 Density (determined according to ISO 1183-1 - Method A).

[0033] Preferably, the multimodal linear low density polyethylene (LLDPE) has an MFR5 (measured according to ISO 1133-1; 190°C, 5 kg load) of 0.45 to 0.80 g / 10 min, more preferably 0.50 to 0.75 g / 10 min and especially 0.55 to less than 0.75 g / 10 min.

[0034] Preferably, the multimodal linear low density polyethylene (LLDPE) has an MFR2 (measured according to ISO 1133-1; 190°C, 2.16 kg load) of 0.05 to 0.25 g / 10 min, more preferably 0.08 to 0.22 g / 10 min and especially 0.10 to 0.19 g / 10 min.

[0035] Preferably, the multimodal linear low density polyethylene (LLDPE) has an MFR of 5 to 25 g / 10 min, more preferably 8 to 21 g / 10 min and especially 10 to 19 g / 10 min. 21 (Measured according to ISO 1133-1; 190°C, 21.6 kg load).

[0036] Preferably, the multimodal linear low density polyethylene (LLDPE) has a Vicat softening point A50 (10N) (determined according to ISO 306) of 95 to 105°C.

[0037] Preferably, the low density polyethylene (LDPE) has a density of 910 to 940 kg / m 3 , more preferably 915 to 930 kg / m 3 , still more preferably 918 to 928 kg / m 3 and especially 920 to 926 kg / m 3 Density determined according to ISO 1183-1 - Method A).

[0038] Preferably, the low density polyethylene (LDPE) has an MFR2 (determined according to ISO 1133-1; 190°C, 2.16 kg load) of 0.05 to 50.0 g / 10 min, more preferably 0.08 to 20.0 g / 10 min and especially 0.1 to 10.0 g / 10 min.

[0039] Preferably, the low density polyethylene (LDPE) has an MFR5 (measured according to ISO 1133-1; 190°C, 5 kg load) of 0.3 to 50.0 g / 10 min, more preferably 0.5 to 20.0 g / 10 min and especially 0.8 to 10.0 g / 10 min.

[0040] Preferably, the low density polyethylene (LDPE) has a melting temperature (determined according to ASTM D 3418) of 100 to 120°C, more preferably 103 to 116°C and especially 105 to 113°C.

[0041] Preferably, the film has a total transmission preferably determined according to ASTM D1003-00 of at least 80%, more preferably at least 85% and in particular at least 90%. It is also preferred that the film has a total transmission preferably determined according to ASTM D1003-00 of at most 100% or at most 99% or at most 95%. In this respect, the total transmission is preferably determined according to ASTM D1003 using a Haze-Gard measuring instrument from BYK-Gardner, wherein a film sample with a minimum radius of 7 cm is used and 5 samples of each sample and a reference sample are measured.

[0042] Preferably, the film has a haze (determined according to ASTM D1003-00) of preferably at least 80%, more preferably at least 82% and in particular at least 84%. It is also preferred that the film has a haze of at most 100% or at most 95% or at most 92%, preferably determined according to ASTM D1003-00. In this regard, the haze is preferably determined according to ASTM D1003 using a BYK-Gardner Haze-Gard measuring instrument, wherein a film specimen with a minimum radius of 7 cm is used, and 5 specimens and a reference specimen of each sample are measured. The skilled person will appreciate that providing sufficient haze in a fairly thin film having a thickness of, for example, 10 to 100 μm or 10 to less than 50 μm or 50 to 100 mm or 70 to 90 μm is particularly challenging.

[0043] Preferably, the film has a total thickness of preferably at least 50 μm, more preferably at least 70 μm, still more preferably at least 90 μm and in particular at least 120 μm. It is also preferred that the film has a total thickness of at most 300 μm, more preferably at most 250 μm, still more preferably at most 220 μm and in particular at most 200 μm. In this regard, it should be understood that if the "total thickness" of the film is mentioned, it refers to the thickness of the monolayer or multilayer film, rather than the thickness of one of the separation layers (such as inner layer, outer layer and intermediate layer) present in the multilayer film. Therefore, when referring to the total thickness of a multilayer film, it refers to the sum of all layers included in the multilayer film.

[0044] Preferably, the film has an average surface roughness Sa measured by optical profilometry of at least 470 nm, preferably at least 515 nm and in particular at least 530 nm. It is also preferred that the film has an average surface roughness Sa measured by optical profilometry of at most 1000 nm, preferably at most 900 nm and in particular at most 800 nm.

[0045] Preferably, the film has a root mean square surface roughness Sq measured by optical profilometry of at least 570 nm, preferably at least 615 nm and in particular at least 630 nm. It is also preferred that the film has a root mean square surface roughness Sq measured by optical profilometry of at most 1100 nm, preferably at most 1000 nm and in particular at most 900 nm.

[0046] Preferably, the film has a surface roughness peak height Sp measured by optical profilometry of at least 2800 nm, preferably at least 3000 nm and in particular at least 3080 nm. It is also preferred that the film has a surface roughness peak height Sp measured by optical profilometry of at most 5000 nm, preferably at most 4500 nm and in particular at most 4000 nm.

[0047] Preferably, the film has a surface roughness valley depth Sv determined by optical profilometry of at least 2300 nm, preferably at least 2450 nm and in particular at least 2550 nm. It is also preferred that the film has a surface roughness valley depth Sv determined by optical profilometry of at most 5000 nm, preferably at most 4000 nm and in particular at most 3500 nm.

[0048] Preferably, the film has a maximum surface roughness height Sz of at least 5100 nm, preferably at least 5400 nm and in particular at least 5600 nm, as measured by optical profilometry. It is also preferred that the film has a maximum surface roughness height Sz of at most 8000 nm, preferably at most 7000 nm and in particular at most 7500 nm, as measured by optical profilometry.

[0049] Alternatively, the film has a lower total thickness of, for example, less than 50 μm, preferably 10 to less than 50 μm and in particular 15 to 45 μm. In this regard, the film preferably has an average surface roughness Sa measured by optical profilometry of 20 to less than 470 nm, more preferably 50 to 450 nm and in particular 80 to 300 nm. Such films preferably have a root mean square surface roughness Sq measured by optical profilometry of 20 to less than 570 nm, more preferably 50 to 500 nm and in particular 80 to 400 nm. Such films preferably have a surface roughness peak height Sp measured by optical profilometry of 500 to less than 2800 nm, more preferably 800 to 2200 nm and in particular 1000 to 1800 nm. Such films preferably have a surface roughness valley depth Sv measured by optical profilometry of 400 to less than 2300 nm, more preferably 700 to 2000 nm and in particular 900 to 1700 nm. Such films preferably have a maximum height Sz of the surface roughness, determined by optical profilometry, of 1000 to less than 5100 nm, preferably 1400 to 4500 nm and in particular 1800 to 4000 nm.

[0050] Preferably, the film comprises at least 80% w / w, more preferably at least 85% w / w of multimodal linear low density polyethylene (LLDPE), based on the total amount of the film. It is also preferred that the film comprises at most 97% w / w, more preferably at most 95% w / w of multimodal linear low density polyethylene (LLDPE), based on the total amount of the film.

[0051] Surprisingly, the inventors have found that suitable films can be provided, wherein the film comprises a reduced amount of cost-intensive low-density polyethylene (LDPE). Preferably, based on the total amount of the film, the film comprises 1 to 30% w / w, more preferably 3 to 20% w / w and in particular more than 5 to 15% w / w of low-density polyethylene (LDPE).

[0052] Preferably, the film comprises at least two layers. In this respect, it is preferred that the one layer comprises a multimodal linear low density polyethylene in the range of 65 to 90% w / w, more preferably 70 to 90% w / w and especially 80 to 90% w / w, based on the total amount of one layer, the multimodal linear low density polyethylene having a molecular weight of 910 to 940 g / cm 3 The present invention has a density of 0.1 g / 10 min (determined according to ISO 1183-1 - method A) and an MFR5 of 0.40 to 0.85 g / 10 min (determined according to ISO 1133-1; 190° C., 5 kg load).

[0053] Preferably, the film comprises at least three layers, more preferably an inner layer, an outer layer and an intermediate layer between the inner layer and the outer layer. In this respect, it is preferred that the intermediate layer comprises at least 65% w / w, more preferably at least 70% w / w and in particular at least 80% w / w of a multimodal linear low density polyethylene having a molecular weight of 910 to 940 g / cm 3 The multimodal linear low density polyethylene comprises a density of 0.1 g / 10 min (measured according to ISO 1183-1 - method A) and an MFR5 of 0.40 to 0.85 g / 10 min (measured according to ISO 1133-1; 190°C, 5 kg load). It is further preferred that the intermediate layer comprises up to 90 % w / w of said multimodal linear low density polyethylene, based on the total amount of the intermediate layer.

[0054] If the film comprises an inner layer, the inner layer preferably comprises at least 80% w / w, preferably at least 90% w / w and in particular at least 95% w / w of a multimodal linear low density polyethylene having a molecular weight of 910 to 940 g / cm 3 The inner layer preferably comprises a multimodal linear low density polyethylene having a density of 910 to 940 g / m2 (measured according to ISO 1183-1 - method A) and an MFR5 of 0.40 to 0.85 g / 10 min (measured according to ISO 1133-1; 190°C, 5 kg load). It is also preferred that the inner layer comprises at most 100% w / w or at most 99% w / w of the multimodal linear low density polyethylene. In a particularly preferred embodiment, the inner layer consists of a multimodal linear low density polyethylene having a molecular weight of 910 to 940 g / m2 3 The present invention has a density of 0.1 g / 10 min (determined according to ISO 1183-1 - method A) and an MFR5 of 0.40 to 0.85 g / 10 min (determined according to ISO 1133-1; 190° C., 5 kg load).

[0055] If the film comprises an outer layer, the outer layer preferably comprises at least 80% w / w, preferably at least 90% w / w and in particular at least 95% w / w of a multimodal linear low density polyethylene having a molecular weight of 910 to 940 g / cm 3 The outer layer preferably comprises a multimodal linear low density polyethylene having a density of 910 to 940 g / m2 (measured according to ISO 1183-1 - method A) and an MFR5 of 0.40 to 0.85 g / 10 min (measured according to ISO 1133-1; 190°C, 5 kg load). It is also preferred that the outer layer comprises at most 100% w / w or at most 99% w / w of the multimodal linear low density polyethylene. In a particularly preferred embodiment, the outer layer consists of a multimodal linear low density polyethylene having a molecular weight of 910 to 940 g / m2 3The present invention has a density of 0.1 g / 10 min (determined according to ISO 1183-1 - method A) and an MFR5 of 0.40 to 0.85 g / 10 min (determined according to ISO 1133-1; 190° C., 5 kg load).

[0056] In a preferred embodiment, the film comprises an inner layer, an outer layer and an intermediate layer between the inner layer and the outer layer, wherein the intermediate layer comprises at least 65% w / w, preferably at least 80% w / w, based on the total amount of the intermediate layer, of a multimodal linear low density polyethylene having a molecular weight of 910 to 940 g / cm 3 The invention relates to a multimodal linear low density polyethylene having a density of 100 to 200 g / cm2 (measured according to ISO 1183-1 - method A) and an MFR5 of 0.40 to 0.85 g / 10 min (measured according to ISO 1133-1; 190°C, 5 kg load) and wherein the inner layer and the outer layer comprise at least 80% w / w, preferably at least 90% w / w and in particular at least 95% w / w, based on the total amount of the respective layer, the multimodal linear low density polyethylene having a molecular weight of 910 to 940 g / cm2 3 The present invention has a density of 0.1 g / 10 min (determined according to ISO 1183-1 - method A) and an MFR5 of 0.40 to 0.85 g / 10 min (determined according to ISO 1133-1; 190° C., 5 kg load).

[0057] If the film includes an inner layer, an outer layer and an intermediate layer,

[0058] The inner layer preferably has a thickness of 10 to 60 μm, more preferably 20 to 50 μm,

[0059] The intermediate layer preferably has a thickness of 30 to 130 μm, more preferably 50 to 100 μm,

[0060] The outer layer preferably has a thickness of 10 to 60 μm, more preferably 20 to 50 μm.

[0061] Preferably, the film has a dart impact (DDI) measured according to ISO 7765-1 of at least 850 g, preferably at least 900 g, more preferably at least 1000 g and in particular at least 1050 g. It is also preferred that the film has a DDI measured according to ISO 7765-1 of at most 2000 g or at most 1800 g or at most 1700 g.

[0062] Preferably, the film has a ratio of tear strength (TD) / tear strength (MD) (both measured according to ISO 6383-2) of less than 2.3, preferably less than 2.2. It is also preferred that the film has a ratio of tear strength (TD) / tear strength (MD) (both measured according to ISO 6383-2) greater than 1.7, preferably greater than 1.8.

[0063] Preferably, the comonomer(s) of the multimodal linear low density polyethylene is selected from C4 to C 20 The alpha olefin is more preferably selected from C4 to C8 alpha olefins, such as butene, hexene, octane.

[0064] The comonomer(s) are preferably present in the multimodal LLDPE in the range of 1 to 20 wt%, more preferably 3 to 15 wt%, even more preferably 5 to 12 wt%, based on the total weight of the multimodal LLDPE.

[0065] The multimodal linear low density polyethylene (LLDPE) used in the present invention is multimodal, i.e. its molecular weight distribution does not comprise a single peak but a combination of two or more peaks centred around different average molecular weights due to the fact that the polymer comprises two or more separately produced components. Such multimodal polymers may be prepared, for example, by two or more stage polymerisation or by using two or more different polymerisation catalysts in one stage polymerisation. Preferably, however, such multimodal polymers are produced by a two or more stage polymerisation process, in particular a slurry polymerisation in a loop reactor followed by a gas phase polymerisation in one or more gas phase reactors, using the same catalyst, for example a metallocene catalyst or a Ziegler-Natta catalyst.

[0066] The multimodal linear low density polyethylene (LLDPE) may be produced using conventional single site catalysis or Ziegler-Natta catalysis as known in the art. Conventional cocatalysts, supports / carriers, electron donors etc. may be used.

[0067] Suitable preferred catalysts are as follows.

[0068] Preferred polymerization catalysts contain magnesium compounds, aluminum compounds and titanium compounds preferably supported on a particulate support. The particulate support may be an inorganic oxide support such as silica, alumina, titania, silica-alumina and silica-titania. Preferably, the support is silica.

[0069] In a preferred embodiment, a Ziegler-Natta catalyst is used to produce a multimodal linear low density polyethylene (LLDPE).

[0070] Preferably, the membrane does not comprise an additional coating-containing layer and / or an additional tie-layer.

[0071] Preferably, the film does not contain inorganic fillers and / or ethylene vinyl acetate (EVA) copolymers.

[0072] The film can be produced by methods commonly used in the art, such as casting or blown extrusion, the latter being preferred.

[0073] The blow extrusion process is described below by way of example.

[0074] The film is produced by extrusion through an annular die, wherein a pressure differential is applied to blow the extruded cylinder into a film and to achieve the desired orientation within the film, ie to build up stress in the cooled film.

[0075] The components of the film (eg, LLDPE) are typically extruded and blown, as is well known in the art.

[0076] Typically, the components of the layers constituting the film will be blown (i.e. (co)extruded) at a temperature in the range of 160°C to 240°C and cooled by blowing a gas (typically air) at a temperature of 10 to 50°C to provide a frost line height of 1 to 8 times the die diameter, preferably 2 to 6 times the die diameter. The stretch ratio should typically be in the range of 1.2 to 7 ((mm) / (mm))*(1 / ((mm) / (mm))), preferably 1.5 to 5 ((mm) / (mm))*(1 / ((mm) / (mm))). The take-off speed may be in the range of 8 to 18 m / min, preferably in the range of 10 to 16 m / min.

[0077] The film forming process steps of the present invention are known and can be carried out on a film production line in a manner known in the art. Such film production lines are commercially available.

[0078] The film, preferably the blown film of the present invention, is preferably not subjected to a subsequent stretching step.

[0079] Example

[0080] Test Method

[0081] a) Density is measured according to ISO 1183-1 - Method A. Sample preparation is carried out by compression moulding according to ISO 1872-2:2007.

[0082] b) Melt flow rate (MFR2, MFR5 and MFR 21 )

[0083] The melt flow rate was measured at 190°C under a load of 2.16 kg (MFR2), 5 kg (MFR5) or 21 kg (MFR 21 The melt flow rate is the amount of polymer in grams which is extruded in 10 minutes at a temperature of 190° C. under loads of 2.16 kg, 5 kg and 21 kg, respectively, using a test apparatus standardized according to ISO 1133-1.

[0084] c) DSC analysis, melting temperature (Tm) and heat of fusion (Hf), crystallization temperature (Tc) and melting enthalpy (Hm): The measurements were performed on 5 to 7 mg samples with a TA Instrument Q2000 differential scanning calorimeter (DSC). The DSC was run in a heating / cooling / heating cycle at a scanning rate of 10°C / min in the temperature range of 0 to +200°C according to ISO 11357 / Part 3 / Method C2. The crystallization temperature (Tc) was determined from the cooling step, while the melting temperature (Tm) and the melting enthalpy (Hm) were determined from the second heating step. The crystallinity was calculated from the melting enthalpy by assuming a Hm value of 209 J / g for fully crystalline polypropylene (see Brandrup, J., Immergut, EH, Eds. Polymer Handbook, 3rd edition, Wiley, New York, 1989; Chapter 3).

[0085] d) Vicat softening point A50 (10N) (determined according to ISO 306)

[0086] The Vicat softening temperature is 1mm under a load of 10N or 50N. 2 The temperature at which a flat-tipped needle penetrates the specimen to a depth of 1 mm. This temperature reflects the expected softening point when the material is used in high temperature applications. The Vicat softening point is measured using an Instron-CEAST HDT VICAT test instrument according to ISO 306, method A50, using a force of 10 N and a heating rate of 50 °C / h. Use 3 specimens per sample with a thickness of 3-6.5 mm and a width and length of at least 10 mm.

[0087] e) Tear (MD and TD)

[0088] The tear resistance of the samples is measured by the Elmendorf method using a Thwing-Albert ProTear device according to ISO 6383-2. This is a method for determining the force required to extend a tear in a specimen by a specified distance from a specified slit. The data obtained by this method are expressed as tear force in Newtons at a specific specimen thickness. The measurement direction can be MD or TD measured in the same way. For comparison purposes, data obtained with film samples of the same thickness must be used.

[0089] f) Tensile modulus (MD and TD) was measured according to ISO 527-2 (crosshead speed = 50 mm / min; 23°C) using injection moulded test specimens (dog bone shape, 4 mm thickness) as described in EN ISO 1873-2.

[0090] g) Dart impact (DDI)

[0091] The DDI of the samples was measured using an INSTRON CEAST dart impact tester according to ISO 7765-1. Dart impact is a method used to evaluate the impact strength or toughness of plastic films.

[0092] Optional Additional Details: This test uses a single dart configuration and a single drop height while varying the dart weight. The method used to analyze the data from this test is called the "Step" method. A series of impacts are performed. If the specimen passes, the dart weight is increased by 30g. If the specimen fails, the dart weight is decreased by 30g. The results from these impacts are used to calculate the impact failure mass - the point at which 50% of the test specimens will fail under this impact, with the impact failure mass calculated to the nearest 1g.

[0093] h) Puncture resistance

[0094] The puncture resistance of the film was measured on a 500N load cell and according to ASTM D5748 using a Zwick-Roell universal testing machine. This test method determines the resistance of polyolefin films to penetration by a probe at a standard low rate, single test speed. The maximum force, breaking force, penetration distance and breaking energy are determined. Five specimens of 150×150 mm geometry are measured per sample.

[0095] i) Surface roughness (profilometry)

[0096] The surface roughness of the film samples was determined using a Bruker Contour GT-K Optical Profiler. The measurements were performed in white light interferometry / vertical scanning interferometry (VSI) mode with a large area aperture of 5x at a vertical resolution of 3nm (rms). At 5x aperture, an area of ​​1250μm x 950μm of the film sample was analyzed. The most important surface roughness information obtained by line or area profile analysis is given below;

[0097] Sa: Average surface roughness, which expresses the height difference of each point compared with the arithmetic mean of the surface as an absolute value.

[0098] S a =∫∫ a |Z(x,y)|dxdy

[0099] Sq: Root mean square roughness, which represents the root mean square value of each ordinal value in a limited area. It is equivalent to the standard deviation of height.

[0100]

[0101] Sp: Peak height, which is the height of the highest peak in the limited area.

[0102] Sv: Maximum trough height, which is the absolute value of the height of the largest trough (or pit) in the defined area.

[0103] Sz: Maximum height, which is Sp+Sv.

[0104] j) Melt strength

[0105] The melt strength of the samples was measured using a GOTTFERT Rheotens 71.97 Elongational Tester with a GOTTFERT Rheograph 25 Capillary Rheometer according to ISO 16790. This method is used to determine the tensile and fracture properties of molten plastics. The method involves measuring the force generated when a molten filament is deformed under defined extrusion temperature and stretching conditions. The test conditions were: 190°C, 0.05mm / s piston speed, 30 / 1L / D die, standard Rheotens wheel with a gap of 0.6mm, and an acceleration of 120mm / s2. A 15mm barrel was used.

[0106] k) Haze and transmittance

[0107] According to ASTM D1003 standard, the haze and transmittance of the samples were measured using a BYK-Gardner Haze-Gard meter. A film sample with a minimum radius of 7 cm was used, and 5 samples of each sample and a reference sample were measured.

[0108] l) Wide-angle X-ray scattering (WAXS)

[0109] A strip of 2.5 cm in length in the machine direction and 1 cm in width in the transverse direction was cut from the blown film for WAXS measurement. The measurements were performed at 3 different sample positions with the x-ray beam oriented in the normal direction of the film surface. WAXS measurements were performed in transmission geometry using a Bruker D8 Discover with a GADDS x-ray diffractometer operating with the following settings:

[0110] X-ray generator: 40 kV and 40 mA; duration: 300 seconds; θ1 = 0° & θ2 = 0° and beam size (collimator): 500 μm.

[0111] The WAXS technique in polymer research is able to distinguish and quantify ordered and disordered states. A monochromatic x-ray beam is collimated through a film sample, and the x-rays are scattered at various angles by the crystal planes. The scattered x-rays are recorded by a 2-dimensional (2D) detector. The crystalline portion of semi-crystalline polyethylene produces a diffraction pattern of several concentric Debye rings or spots, while the amorphous portion of the semi-crystalline polymer produces a diffraction pattern of diffuse nature consisting of halos. The strongest scattering in semi-crystalline polyethylene is produced by the (110) and (200) planes at 2θ = 21.5° and 23.8°, respectively.

[0112] Anisotropy in polymers can be obtained by applying mechanical stress to solid polymers or during processing of melts and / or during cooling. The presence of anisotropy can be estimated from the scattering pattern due to the presence of arcs and spots instead of Debye rings. The shorter the arcs, the higher the degree of orientation. In polyethylene film samples, reflections from the (110) plane and the (200) plane can vary as a function of Chiχ.

[0113] To obtain the scattered intensity as a function of Chiχ, the two-dimensional scattering patterns of the (110) and (200) planes were integrated between χ = -14° and 340°. These patterns are shown graphically in FIG2 .

[0114] For a uniaxially oriented system, the Hermans orientation factor (f H ) quantifies the orientation state as follows: (Alexander LE, X-ray diffraction methods in polymer science. New York: John Wiley & Sons; 1969). here, is the angle between the unit whose orientation state is of interest (e.g., polymer chain axis and crystallographic axis) and a reference axis (e.g., machine direction MD). H = 1 indicates perfect orientation, f H = 0 indicates random orientation, while f H = -0.5 indicates an orthogonal orientation. All orientations are described relative to the same reference axis (MD).

[0115] Stein extended Hermans treatment for axial orientation by establishing the following three equations to specify the degree of orientation of each of the crystal axes relative to a reference direction Z (MD):

[0116] as well as

[0117] For an orthorhombic unit cell, f a 、f b and f c Specifically, they are related to each other through the Pythagorean theorem. a +f b +f c =0.

[0118] The value of is limited to:

[0119]

[0120] Hermans a-axis orientation factor f a Depend on Given, where Hermans b-axis orientation factor f b Depend on Given, where

[0121] Using the orthogonal relation f a +f b +f c = 0 to calculate the Hermans c-axis orientation factor f relative to the machine direction (reference Z-axis, MD) c .

[0122] Material

[0123] FB2230 is a multimodal linear low density polyethylene (LLDPE) produced by a Ziegler-Natta catalyst with a density (determined according to ISO 1183-1 - Method A) of 923 kg / m 3, MFR2 (measured according to ISO 1133-1; 190°C, 2.16 kg load) is 0.25 g / 10 min, MFR5 (measured according to ISO 1133-1; 190°C, 5 kg load) is 1.0 g / 10 min, MFR 21 (determined according to ISO 1133-1; 190°C, 21.6 kg load) was 22 g / 10 min, the melting temperature (determined according to ISO 11357 / 03) was 124°C, and the Vicat softening point A50 (10N) (determined according to ISO 306) was 101°C.

[0124] LLDPE-A is a multimodal linear low density polyethylene (LLDPE) produced by a Ziegler-Natta catalyst with a density (determined according to ISO 1183-1 - Method A) of 921 kg / m 3 , MFR2 (measured according to ISO 1133-1; 190°C, 2.16 kg load) is 0.17 g / 10 min, MFR5 (measured according to ISO 1133-1; 190°C, 5 kg load) is 0.70 g / 10 min, MFR 21 (determined according to ISO 1133-1; 190°C, 21.6 kg load) was 16 g / 10 min, the melting temperature (determined according to ISO 11357 / 03) was 123°C, and the Vicat softening point A50 (10N) (determined according to ISO 306) was 100°C.

[0125] Lotrène FB3003 is a low density polyethylene (LDPE) with a density (measured according to ISO 1183-1 - Method A) of 920 kg / m 3 , MFR5 (measured according to ISO 1133-1; 190°C, 5 kg load) is 1.2 g / 10 min, MFR2 (measured according to ISO 1133-1; 190°C, 2.16 kg load) is 0.3 g / 10 min, and the melting temperature (measured according to ASTM D 3418) is 109°C.

[0126] Production of LLDPE-A

[0127] a) Catalyst

[0128] The polymerization catalyst used for the polymerization of the exemplary LLDPE-A of the present invention was prepared according to Example 1 of EP 1 378 528 A1.

[0129] b) Polymerization of LLDPE-A

[0130] In the prepolymerization stage, the volume is 50dm 3The first loop reactor was operated at 70° C. and 64 bar pressure. To produce the prepolymerization fraction, ethylene, 1-butene and hydrogen were added. In addition, a polymerization catalyst prepared according to the above description and a triethylaluminum (TEA) cocatalyst were introduced into the reactor.

[0131] The conditions in the reactor are shown in Table A.

[0132] The polymer slurry was withdrawn from the first loop reactor and transferred to a 500 dm 3 The second loop reactor was operated at 85°C and 64 bar pressure. Ethylene, 1-butene and hydrogen were introduced into the reactor. No additional catalyst feed was introduced into the reactor. The conditions in the reactor are shown in Table A.

[0133] The polymer slurry is withdrawn from the second loop reactor and transferred to a flasher operated at a pressure of 3 bar and a temperature of 70° C., in which hydrocarbons are substantially removed from the polymer. The polymer is then introduced into a gas phase reactor operated at a temperature of 78.5° C. and a pressure of 19.6 bar. In addition, ethylene, 1-butene and hydrogen are introduced into the reactor. The conditions are shown in Table A.

[0134] The obtained polymer was purged with nitrogen (about 50 kg / h) for one hour, stabilized with 1000 ppm of Irganox 1010 and Irgafos 168 and 1000 ppm of calcium stearate, and then extruded into pellets in a counter-rotating twin-screw extruder CIM90P (manufactured by Japan SteelWorks) so that the throughput was 223 kg / h and the screw speed was 323 rpm.

[0135] Table A Polymerization conditions of the present invention exemplary LLDPE-A

[0136] LLDPE-A Prepolymerization temperature ℃ 70 pressure -bar 64 Split ratio wt-% 1.4 H2 / C3 feed ratio kg / ton C3 0.2 C4 / C2 feed ratio kg / ton C2 40 Ring pipe: temperature ℃ 85 pressure -bar 64 C2-Concentration mol% 2.43 H2 / C2 molar ratio mol / kmol 350 C4 / C2 molar ratio mol / kmol 641 C4 / C2 feed ratio kg / ton C2 47-48 Split Ratio wt-% 37.6 <![CDATA[MFR2]]> g / 10min 270-340 density <![CDATA[kg / m 3 ]]> 950.5-951.5 Gas phase: temperature ℃ 78.5 pressure -bar 19.6 C2-Concentration mol% 3.6 H2 / C2 molar ratio mol / kmol 5.8-6.1 C4 / C2 molar ratio mol / kmol 765 C4 / C2 feed ratio kg / ton C2 139-140 Split Ratio wt-% 61.0 Density (base resin) <![CDATA[kg / m 3 ]]> 920.0-921.2 <![CDATA[MFR5 (Base Resin)]]> g / 10min 0.60-0.74

[0137] Manufacturing and testing of greenhouse films

[0138] Greenhouse films with a 3-layer multilayer structure as given in Table 1 were produced and tested. The surface layers contained only LLDPE, while the core layer (also called middle layer) contained a blend of LLDPE and LDPE. The inventive film contained LLDPE-A, while the reference film contained LLDPEFB2230. The processing conditions for the production of a 3-layer multilayer structure film with a thickness of 150 μm using a Polyrema blown film line at Borouge Innovation Centre are given in Table 2. It can be mentioned that the data from the Polyrema line are consistent with the commercial values ​​obtained by large processors.

[0139] Films containing 30% w / w LDPE (Ref. 4 and IE 3) were produced according to the process listed in Table 2 and the dosage was adjusted respectively.

[0140] Furthermore, based on the process according to Table 2, two comparative 3-layer mono-material films with similar thickness (150 μm) were produced, namely 100% FB2230 (Ref. 2) or 100% LLDPE-A (Ref. 3), wherein 100% of the corresponding LLDPE was also used for the core layer.

[0141] Table 1 Configuration of the greenhouse film of the present invention and reference

[0142] Greenhouse membrane structure Reference film Film of the present invention External: LLDPE resin FB2230 LLDPE-A Core: blend of LLDPE and LDPE FB2230+FB3003 LLDPE-A+FB3003 Inner: LLDPE resin FB2230 LLDPE-A

[0143] Table 2 Processing conditions for greenhouse film production on Polyrema lines

[0144]

[0145] The properties of the reference films and the inventive films are shown in Table 3. The properties of comparative 3-layer mono-material films (i.e., Ref. 2: 100% FB2230 or Ref. 3: 100% LLDPE-A) with similar thickness (150 μm) are also given. The ratio of TD / MD tear to tensile modulus was estimated as a measure of the degree of inhomogeneity and is shown in Table 3 for all samples.

[0146] Table 3 Summary of the properties of the inventive and reference greenhouse films; na* means "not available".

[0147]

[0148]

[0149] Tear: Comparison of the mono-material films shows that the MD and TD properties are not equal due to the inevitable orientation effects of the ZN LLDPE during blown film processing. The mono-material films Ref.2 and Ref.3 show a similar ratio of TD / MD tear of 1.6. However, the addition of LDPE in the core layer leads to an increase in this inhomogeneity. For the reference films, a large difference in MD and TD tear properties is observed, and this difference increases with increasing LDPE content. For Ref.1 with 15% LDPE in the core, the TD / MD tear ratio is 2.8. For Ref.4 with 30% LDPE in the core, the TD / MD tear ratio is 3.9, indicating that the MD and TD properties differ almost fourfold. In contrast, for the inventive films with LLDPE-A, the difference is relatively low, with a TD / MD tear ratio of 2.1 for IE1 (and 2.0 for IE3). This is closer to the mono-material films than the reference films (TD / MD ratios of 2.8 and 3.9, respectively). Furthermore, this ratio did not increase with increasing LDPE content in the core layer, which was the same as the case of the reference film.

[0150] Tensile modulus: The ratio of TD / MD tensile modulus is 1.29 and 1.24 for the mono-material films Ref.2 and Ref.3, respectively. Although this ratio is similar for the reference greenhouse films with 15% and 30% LDPE in the core layer, an improvement can be seen for the films of the invention. Increasing the amount of LDPE in the core layer to 30% further improves the homogeneity of this property.

[0151] Dart Drop Impact (DDI): An improvement in the DDI of the inventive films can be seen compared to the reference films. For samples with 15% LDPE in the core layer, up to 38% increase in DDI was achieved in the inventive films.

[0152] Puncture resistance: A slight improvement in puncture resistance is seen for the inventive film with 30% LDPE in the core layer.

[0153] Optical properties: Improve diffuse scattering or haze performance without reducing total transmittance. This is especially useful for greenhouse films with smaller thicknesses (e.g. 80 μm).

[0154] Higher surface roughness: The inventive film can be seen to have a slightly increased surface roughness, which contributes to increased haze (and internal scattering).

[0155] In summary, even at a relatively low LDPE content of 15 wt.% in the core layer, the improvements in the properties listed above are achieved.

[0156] 1. MFR, density and melt strength of LLDPE and LDPE blends

[0157] Blends of 85% LLDPE (FB2230 or LLDPE-A) with 15% LDPE (FB3003) were analyzed. MFR values ​​and density are given in Table 4, while melt strength results are given in Table 5. Blends with LLDPE-A show significantly lower MFR compared to blends with FB2230. The melt strength of blends based on LLDPE-A is also higher (see also Figure 1 ).

[0158] Table 4 MFR and density results of core layer composition

[0159]

[0160] Table 5 Melt strength results of core layer composition

[0161]

[0162] 2. Orientation through WAXS

[0163] Analysis of orientation was performed by wide angle X-ray scattering (WAXS). As can be seen in Figure 2, the present invention shows reduced orientation in the machine direction. The average Herman orientation distribution functions of the reference and the present invention film samples with 30% LDPE are given in Table 6. Overall, it can be seen that the orientation of the present invention film is more uniform in three directions compared to the reference film.

[0164] Table 6 Average Herman orientation distribution function

[0165] sample fa fb fc IE3 (30% LDPE in the core layer) 0.072 -0.146 0.074 Ref.4 (30% LDPE in the core layer) -0.216 -0.015 0.231

[0166] 3. Lamellar morphology

[0167] Typically, the surface layers in greenhouse films containing Borstar LLDPE have a unique matte finish, providing a high 3D surface roughness and, accordingly, providing enhanced haze or diffuse scattering properties of the product. Without being bound by any theory, it is assumed that in the core layer, the interaction of LDPE and LLDPE lamellae during blown film processing and the resulting morphology formation play a key role in the final properties of the greenhouse film product. The morphology of the surface layers and core layers was analyzed in detail by scanning electron microscopy, and the results can be seen in Figures 3(a) and (b). Compared to the reference film Ref.1, the surface layer morphology of the inventive film IE1 is dominated by larger or long-range spherulites, and these spherulites are composed of highly meshed linear lamellae.

[0168] Significant differences can be seen in the lamellae morphology of the core layer blended with LDPE. In the reference films Ref.1 and Ref.4 (not depicted in Figure 3) and the inventive films IE1 and IE3 (not depicted in Figure 3), a continuous lamellae network structure can be seen. In other words, discrete spherulite structures as in the non-blended LLDPE surface layers are not seen in the blended layers. In the reference film Ref.4, highly aligned lamellae in the transverse direction can be seen, which can be due to the transverse stretching during the bubble formation in the film processing step. Between these well-aligned lamellae, interlocking features can be seen. In the films of the present invention, the morphology of the film with 15% LDPE is dominated by a continuous network of highly interlocked lamellae with slight alignment in the transverse direction. These orientation observations are consistent with the WAXS results.

[0169] Therefore, the core morphology of the inventive film IE1 plays a key role in providing uniform mechanical properties as well as balancing haze and total light transmittance.

[0170] 4. Surface roughness:

[0171] The surface roughness analysis of the reference film and the film of the present invention was done by optical profilometry. As can be seen from Table 3 above, the film of the present invention shows a higher average surface roughness (compare Ref.1 with IE1, and Ref.4 with IE3). This can be attributed to the larger or long-range spherulites visible on the surface of the film of the present invention (Fig. 3 (a)), resulting in a domain coarsening effect, and thus an increase in surface roughness. As explained previously, an increase in the surface roughness of the film results in higher surface scattering and higher haze.

Claims

1. A single-layer or multi-layer film comprising: At least 70% w / w of a multimodal linear low density polyethylene (LLDPE), based on the total amount of the film, the multimodal linear low density polyethylene (LLDPE) having a molecular weight of 910 to 940 kg / m 3 a density of 0.1 g / 10 min (measured according to ISO 1183-1 - method A) and an MFR5 of 0.40 to 0.85 g / 10 min (measured according to ISO 1133-1; 190° C., 5 kg load), and Low-density polyethylene (LDPE), in, The film has a dart impact (DDI; measured according to ISO 7765-1) of at least 800 g; a tear strength MD of at least 12 N (measured according to ISO 6383-2); and a ratio of tear strength (TD) / tear strength (MD) (both measured according to ISO 6383-2) of less than 2.

5.

2. The film according to claim 1, wherein The film is an agricultural film, preferably a greenhouse film.

3. A membrane according to any one of the preceding claims, wherein The total transmission determined according to ASTM D1003-00 is at least 80%, preferably at least 85%, and in particular at least 90%.

4. A membrane according to any one of the preceding claims, wherein The haze (determined according to ASTM D1003-00) is at least 80%, preferably at least 82%, and in particular at least 84%.

5. A membrane according to any one of the preceding claims, wherein The average surface roughness Sa determined by optical profilometry is at least 470 nm, preferably at least 515 nm, in particular at least 530 nm; and / or wherein the root mean square surface roughness Sq determined by optical profilometry is at least 570 nm, preferably at least 615 nm, in particular at least 630 nm; and / or wherein the surface roughness peak height Sp determined by optical profilometry is at least 2800 nm, preferably at least 3000 nm, and in particular at least 3080 nm; and / or wherein the surface roughness trough depth Sv measured by optical profilometry is at least 2300 nm, preferably at least 2450 nm, and in particular at least 2550 nm; and / or wherein the surface roughness maximum height Sz measured by optical profilometry is at least 5100 nm, preferably at least 5400 nm, and in particular at least 5600 nm.

6. A membrane according to any one of the preceding claims, wherein The film comprises at least 80% w / w, preferably at least 85% w / w of the multimodal linear low density polyethylene (LLDPE), based on the total amount of the film.

7. A membrane according to any one of the preceding claims, wherein The film comprises 1 to 30% w / w, preferably 3 to 20% w / w, more preferably 5 to 15% w / w of the low density polyethylene (LDPE), based on the total amount of the film.

8. A membrane according to any one of the preceding claims, wherein The film comprises at least two layers, and wherein, based on the total amount of one layer, the one layer comprises in the range of 65 to 90 % w / w of the multimodal linear low density polyethylene, the multimodal linear low density polyethylene having a g / cm 3 The present invention has a density of 0.1 g / 10 min (determined according to ISO 1183-1 - method A) and an MFR5 of 0.40 to 0.85 g / 10 min (determined according to ISO 1133-1; 190° C., 5 kg load).

9. The film according to claim 8, wherein The film comprises an inner layer, an outer layer and an intermediate layer between the inner layer and the outer layer, wherein the intermediate layer comprises at least 65% w / w, preferably at least 80% w / w, based on the total amount of the intermediate layer, of a multimodal linear low density polyethylene having a molecular weight of 910 to 940 g / cm 3 The present invention has a density of 0.1 g / 10 min (determined according to ISO 1183-1 - method A) and an MFR5 of 0.40 to 0.85 g / 10 min (determined according to ISO 1133-1; 190° C., 5 kg load).

10. The film according to claim 9, wherein The inner and outer layers comprise at least 80% w / w, preferably at least 90% w / w and in particular at least 95% w / w of a multimodal linear low density polyethylene having a molecular weight of 910 to 940 g / cm 3 The present invention has a density of 0.1 g / 10 min (determined according to ISO 1183-1 - method A) and an MFR5 of 0.40 to 0.85 g / 10 min (determined according to ISO 1133-1; 190° C., 5 kg load).

11. The film according to claim 8 or 9, wherein The inner layer has a thickness of 10 to 60 μm, preferably 20 to 50 μm, The intermediate layer has a thickness of 30 to 130 μm, preferably 50 to 100 μm, and The outer layer has a thickness of 10 to 60 μm, preferably 20 to 50 μm.

12. A membrane according to any one of the preceding claims, wherein The film has a DDI determined according to ISO 7765-1 of at least 850 g, preferably at least 900 g, more preferably at least 1000 g, and especially at least 1050 g.

13. A membrane according to any one of the preceding claims, wherein The film has a ratio of tear strength (TD) / tear strength (MD) (both determined according to ISO 6383-2) of less than 2.3, preferably less than 2.

2.

14. A membrane according to any one of the preceding claims, wherein The comonomer(s) of the multimodal linear low density polyethylene is selected from C4 to C 20 Alpha olefins.

15. A membrane according to any one of the preceding claims, wherein The film does not comprise an additional coating-containing layer and / or an additional tie layer.

Citation Information

Patent Citations

  • A process for the production of a linear low-density polyethylene composition

    EP1378528A1